2015
DOI: 10.3390/ijerph121012324
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Effective Dose Assessment Based on Background Outdoor Gamma Exposure in Chihuahua City, Mexico

Abstract: Determining ionizing radiation in a geographic area serves to assess its effects on a population’s health. The aim of this study was to evaluate the spatial distribution of the background environmental outdoor gamma dose rates in Chihuahua City. This study also estimated the annual effective dose and the lifetime cancer risks of the population of this city. To determine the outdoor gamma dose rate in air, the annual effective dose and the lifetime cancer risk, 48 sampling points were randomly selected in Chihu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Outside the country, Zarghani and Jafari (2017) recorded low range radiation doses in Birjand, Iran. In Chihuahua City, Mexico, Luevano-Gurrola et al (2015) observed high outdoor gamma dose rates ranging from 113 to 310 ηGyh -1 . High radiation levels and doses are detrimental to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Outside the country, Zarghani and Jafari (2017) recorded low range radiation doses in Birjand, Iran. In Chihuahua City, Mexico, Luevano-Gurrola et al (2015) observed high outdoor gamma dose rates ranging from 113 to 310 ηGyh -1 . High radiation levels and doses are detrimental to human health.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime cancer risk (LTCR) was obtained by Equation (6) [11,12]: LTCR=AED×DL×RFSE where DL is the duration of lifetime, 70 years; and RFSE is the risk factor for stochastic effects of the common population, 0.055/Sv [12]. …”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, the dose contribution from technologically enhanced naturally occurring radioactive materials is increasing [7,8]. The worldwide annual effective dose to the public from natural radiation exposure is 2.4 mSv [9], while it is 3.1 mSv in China, which increased from 2.3 mSv in 1990s [10,11,12]. The demand for uranium resources in China is increasing with the development of nuclear power industries [9,13,14] and the rising price of uranium internationally [15].…”
Section: Introductionmentioning
confidence: 99%
“…A háttérsugárzást tekintve összesen évi 2,4 mSv sugárzás éri szervezetünket természetes sugárforrások révén, míg a mesterséges sugárforrások révén 0,4 mSv nagyságú sugárterheléssel kell számolnunk. Azok a betegek, akik betegségükből adódóan időközönként ismételt, orvosi képalkotás segítségét igénylő felvételezésre vannak szorulva, 100 mSv vagy akár magasabb kumulatív dózisnak vannak kitéve az ismételt vizsgálatokból adódóan [8,9].…”
Section: Introduction and Aimunclassified